The research into head injury criteria dependence on car speed - Pelenytė-Vyšniauskienė, Lina; Jurkauskas, Algirdas (Transport, 2007)
There are many ways of car collisions which depend on car motion modes before and after crashes, speed, kinds of baskets, their heights, weights and rigidity. The machinery of the occupant's movement at the moment of the crash is even more difficult. In order to find out precisely the chance of body injury, it is important to measure not only parameters that were mentioned above but also occupant's height, weight, age, position of sitting, condition of body, whether there was any protection system used. The largest number of car crashes happen at the moment of Frontal Crash. This article's aim is to analyse the types of Frontal Crashes and their repartition, to diagnose what part in occupant's safety the protection system's use takes, and also to analyse head injury coefficient dependence on car speed and show critical injuries and fatality limits in cases when driver is driving with no seat‐belts in and while the car is without airbag. The research is done at the moment of ideal Frontal Crash by simulating distance from the occupant body to the wheel in different types of baskets.First Published Online: 27 Oct 2010